Angiopoietin-Like Proteins: A Comprehensive Look - Santulli, Gaetano (Frontiers in Endocrinology, 2014)
Angiopoietin-like proteins (ANGPTLs) are a family of proteins structurally similar to the angiopoietins. To date eight ANGPTLs have been discovered, named ANGPLT1 to ANGPLT8. Emerging evidence implied a key role for ANGPTLs in the regulation of a plethora of physiological and pathophysiological processes. Most of ANGPTLs exhibit multibiological properties, including established functional roles in lipid and glucose metabolism, inflammation, hematopoiesis and cancer. This report represents a systematic and updated appraisal of this class of proteins, focusing on the main features of each ANGPLT.